2022
DOI: 10.1002/jrsm.1611
|View full text |Cite
|
Sign up to set email alerts
|

Commercial funding and estimated intervention effects in randomized clinical trials: Systematic review of meta‐epidemiological studies

Abstract: We investigated to which degree commercial funding is associated with estimated intervention effects in randomized trials. We included metaepidemiological studies with published data on the association between commercial funding and results or conclusions of randomized trials. We searched five databases and other sources. We selected one result per metaepidemiological study, preferably unadjusted ratio of odds ratios (ROR), for example, odds ratio(commercial funding)/odds ratio(noncommercial funding).We pooled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, we did not have sufficient data to do a rigorous evaluation so future studies may look into this difference in information denseness more systematically. Aside from ethics practices, we believe the effect of commercial funding on patient registries is an interesting area of research in and of itself given that the literature so far has focused more on the difference between commercial and non-commercial clinical trials (e.g., Camps, Rodríguez, and Agustí, 2018; Nejstgaard, Laursen, Lundh, and Hróbjartsson, 2023; Schott et al, 2010). One could for example check whether commercially funded registries provide less or more guidance with regard to research transparency (i.e., whether they mandate studies to be preregistered or results to be shared), and whether studies from commercial registries less often or more often contain statistically significant results.…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not have sufficient data to do a rigorous evaluation so future studies may look into this difference in information denseness more systematically. Aside from ethics practices, we believe the effect of commercial funding on patient registries is an interesting area of research in and of itself given that the literature so far has focused more on the difference between commercial and non-commercial clinical trials (e.g., Camps, Rodríguez, and Agustí, 2018; Nejstgaard, Laursen, Lundh, and Hróbjartsson, 2023; Schott et al, 2010). One could for example check whether commercially funded registries provide less or more guidance with regard to research transparency (i.e., whether they mandate studies to be preregistered or results to be shared), and whether studies from commercial registries less often or more often contain statistically significant results.…”
Section: Discussionmentioning
confidence: 99%
“…We have not adjusted the analyses for a combination of potential confounders, and confounding by other unknown or unmeasured factors could have affected our results. For example, although not measured, most of these trials were probably industry‐sponsored, which may also introduce bias 29,30 …”
Section: Discussionmentioning
confidence: 99%
“…For example, although not measured, most of these trials were probably industry-sponsored, which may also introduce bias. 29,30 We introduced heterogeneity by including three clinical specialties (six diseases) instead of restricting the eligibility criteria to one. However, this allowed a greater sample size and more power.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The items that we found to be frequently not reported were related to administrative and methodological issues with a potential impact on systematic review findings. For example, commercial funding source may impact on conclusions of systematic reviews [17], and a recent systematic review found a potential differential impact depending on whether a commercial funder had an influence on the design, conduct, analysis, or reporting of randomized trials [18]. Therefore, merely stating the source of funding may not be sufficient, and if systematic review protocols do not report the role of the sponsor (item 5c), readers may not be able to adequately assess the potential impact on the findings.…”
Section: Meaning Of Our Studymentioning
confidence: 99%